How to motivate planners to participate in community micro-renewal: An evolutionary game analysis - Wang, Dong; Wu, Meiling; Qu, Jiulong; Fan, Yuncui (Frontiers in Psychology, 2022)
In China, grassroots governments have attempted to introduce community planners into community micro-renewal, using their expertise to guide the design and implementation of community micro-renewal. However, there are still issues to be studied and resolved, such as how to effectively play the role of community planners and coordinate the interests of multiple subjects. This study constructs an evolutionary game model of the behavior of multiple subjects (grassroots government, community planners, and community residents) with the participation of community planners, establishes the payment functions of both sides of the game under different choice strategies, explores evolutionary stabilization strategies by replication dynamic equations, and analyses the conditions for the multi-party evolutionary game to reach the ideal stable state. The study finds that: (1) The financial subsidies provided by the grassroots government to community planners positively affect the behavioural choices of community planners to a certain extent. (2) The path of the tripartite evolutionary game between the grassroots government, residents, and community planners to reach the ideal stability (incentive, active participation, and positive promotion). (3) The project benefits obtained by community planners in promoting community micro-renewal can effectively promote positive behavioural choices of community planners.